A relational approach to leadership for multi-actor governance - Marc Craps; Inge Vermeesch; Art Dewulf; Koen Sips; Katrien Termeer; René Bouwen (Administrative Sciences, 2019)
Multi-actor governance, in which a broad mix of actors collaborates to deal with complex societal problems, requires a leadership approach that can take into account the dynamic interdependencies between the involved actors. A relational approach to leadership, focusing on processes and practices, is more adequate for that purpose than approaches focusing on individuals and positions. Complexity leadership theory offers such a relational approach to leadership within organizations. In this article, we use complexity leadership theory to capture the emergent leadership processes between organizations. We focus on the characteristics of the informal relations between representatives of different organizations that enable dealing with the often-conflicting goals and values in multi-actor governance. The case of a landfill mining initiative for sustainable materials governance is used as an illustration to clarify the main concepts and arguments.
Keywords: 350; relational approach; inter-organizational collaboration; multi-actor governance; complexity leadership theory; landfill mining